Surface and interlayer structure of vermiculite intercalated with methyl viologen - Kulhánková, Lenka; Capková, Pavla; De Valle, Veronika Ramirez; Poyato, Juan; Pérez-Rodríguez, Jose Luis; Lerf, Anton (Journal of molecular modeling, 2008)
Molecular modeling using empirical force field revealed the differences between the surface and interlayer arrangement of the dye guest molecules in vermiculite intercalated with the divalent methyl viologen cation (MV(2+)). Conformation and anchoring of MV(2+) cations on the silicate layer in the interlayer space of vermiculite host structure is different from that on the crystal surface. A preferential position has been found for the anchoring of guests on the silicate layer. Anyway the arrangement of guests in the interlayer space as well as on the crystal surface exhibits a high degree of disorder due to a certain flexibility in guest molecules arrangement and first of all due to the presence of water molecules in the interlayer space. The presence of water disturbs not only the regularity in guest positions and orientations but also in conformation of guest molecules in the interlayer space of the host structure.
Keywords: molekulární modely; molekulární konformace; Models, Molecular; silikáty hliníku; Paraquat; Molecular Conformation; X-Ray Diffraction; difrakce rentgenového záření; paraquat; Aluminum Silicates